===================================================
Explanation:
Everywhere you see an x, replace it with -5. Then use the order of operations PEMDAS to simplify
[tex]f(x) = -x^2 - 7x - 5\\\\f(-5) = -(-5)^2 - 7(-5) - 5\\\\f(-5) = -(25) - 7(-5) - 5\\\\f(-5) = -25 + 35 - 5\\\\f(-5) = 10 - 5\\\\f(-5) = 5\\\\[/tex]
Keep in mind that for the x^2 term, you are squaring all of x = -5, which includes the negative as well. So that means
x^2 = (-5)^2 = (-5)*(-5) = 25
but sticking a negative out front makes
-x^2 = -(-5)^2 = -25